Microstructure changes in welded duplex stainless steel and their effects on hardness and corrosion resistance - Melad, Mohamed S.; Gebril, Mohamed A.; Shuaeib, Farag M.; Elrabei, Thabet M.; Elabar, Dawod (Journal of Mining and Metallurgy, Section B: Metallurgy, 2025)
Duplex stainless steel (DSS) is extensively employed in a range of applications because it contains equal proportions of the two phases, ferrite and austenite, as well as a specific percentage of alloying elements. These combined benefits provide the material with superior strength, corrosion resistance, and good welding capacity. During the welding process of DSS, equal amounts of both phases are disrupted, resulting in precipitation. To investigate this phenomenon, this study aims to analyze the effect of changes in welding current by adding 10% N2 with Ar (as a shielding gas) on microstructure changes of DSS weldment. The changes were evaluated through the hardness and corrosion resistance. The study found that by increasing welding current, the Cr2N precipitates disappear in the WZ, with a small amount appearing only in the HAZ. However, the very low welding current causes the formation of Cr2N precipitates in both the WZ and HAZ. The results indicate a direct relationship between the volume fraction of austenite and the welding current. Reducing the welding current increases the hardness of DSS welds due to a higher ferrite volume fraction. Moreover, the corrosion resistance of DSS weldment improves with an increase in the welding current due to the increase in the amount of austenite phase.
Keywords: duplex stainless steel; TIG welding process; Cr2N precipitation; microhardness; corrosion resistance